Bone Metabolism Changes after Laparoscopic Greater Curvature Plication. A One-Year Study - A. O. Nykonenko; Ye. I. Gaidarzh; M. Bužga (Zaporožskij Medicinskij Žurnal)
In addition to the positive effect of weight loosing after bariatric surgery, the post-operative period is often associated with significant changes in bone metabolism. Aim. The aim of this study was to examine changes in bone turnover markers and indicators of dual-energy X-ray absorptiometry (DXA) within 12 months after laparoscopic greater curvature plication (LGCP). Materials and methods. We studied 54 patients from class III obesity who underwent LGCP. The average preoperative weight of the patients was 125,519.1 kg, and BMI of 43.04.9 kg/m2. The gender distribution of the cohort was 35.2% man and 64.8% women. At three time points after the operation (at 3, 6 and 12 months) control examination was conducted that included DXA and markers of bone metabolism. Results. After the surgical treatment we registered significant reduction of all the anthropometric indicators (0.05; EWL12 45.8±18.8%; EBL12 55.1±23.4%). According to the controlled studies on the 12th months, a significant increase in bone turnover markers was revealed (0.05; CTX, P1NP, OC, OPG, VTD) and reducing of PTH (0.05). The measure of DXA on the 12th month of observation showed no significant changes in bone metabolism. Strong positive correlation was uncovered between markers of bone metabolism: CTX / P1NP (r=0.790, p=0.000), CTX/OC, P1NP/OC (r=0.7, p=0.000), minor correlation between PTH/OC (r=0.249, p=0.027). We also report a minor and weak negative correlation between the markers of bone metabolism (CTX, P1NP, OC and VTD) and anthropometric data. Conclusions. Twelve months post LGCP markers of bone turnover (CTX, P1NP, OC, OPG, VTD) were significantly increased. The increased level of VTD is associated with the loss of FAT. Also the change in DXA was detected.